A Quick Review of Security Issues in Telemedicine - Razali R.A.; Jamil N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Patient treatment; Security of data; Advanced technology; Confidential data; Developed countries; Medical services; Security countermeasures; Security mechanism; Telemedicine services; Telemedicine systems; Telemedicine